Level of knowledge and perception of palliative care among anesthesiology residents in Peruvian hospitals - Yóplac-López, Karin J. (2023)
Objective. To analyze the level of knowledge and perception of palliative care among anesthesiology residents in three public hospitals in Lima. Methods. An observational study was conducted, evaluating anesthesiology residents through a questionnaire (Paliative Care Knowlege Test, Spanish version) and five opinion questions applied between June and July 2021. The questionnaire, validated by experts, investigated aspects such as training received in palliative care, previous training, inclination to work in multidisciplinary teams and interest in future specialization in palliative care. Results. Forty resident physicians participated. Sixty-five percent were female and 95% were in the age range of 24 to 40 years. Sixty percent had a medium level of knowledge and 40% high. All of them emphasized the importance of the anesthesiologist's role in palliative care, 50% expressed feeling insufficiently or barely regularly prepared in the subject. A total of 77.5% indicated that they had not received specific training on the subject. In addition, all respondents stated that they considered training in this area to be essential, and 62.5% showed interest in further training or specialization in the future. Conclusions. There is an insufficient level of knowledge and training in palliative care among anesthesiology residents in Peruvian hospitals, despite the recognition of the importance of the area. The need to develop and integrate educational programs is highlighted.